Assessment of Anxiety Status and its Impact on Academic Performance of Undergraduate Medical Students of Bangladesh (Bangladesh Journal of Medical Education, 2025)
Background: Mental health is essential for the well-being of both individuals and communities. Undergraduate medical students travel medical course with tremendous psychological stress because of new environment, language difficulties, curricular overload and frequent examinations. This may hamper their academic performance and mental strength. This study aimed to observe the anxiety status and academic performance of undergraduate medical students of Bangladesh. Methods: This cross-sectional study was performed among 1921 undergraduate medical students from five medical colleges in Bangladesh, who were selected using convenience sampling method. The study was conducted from July 2023 to June 2024. For assessment of anxiety level generalized anxiety disorder 7 (GAD 7) questionnaire was used. The academic performance of the students was self-reported by students as passed (regular/irregular) MBBS professional examinations. Results: The mean score to different questions related to determine their anxiety status were ranged from 31.83% to 39.5%.  It was found that out of 1921 medical students, 40.6%, 29.6%, 17.9% and 11.9% had minimal, mild, moderate and moderately severe anxiety respectively. Different categories of anxiety level were found significantly higher among the female participants and in first academic phase.  Majority of the participants passed regularly (>90%) in their professional examinations. Conclusion: Based on the findings of the present study it can be concluded that undergraduate medical students suffer from varying degrees of Anxiety. Different socio-demographic variables have found significantly associated with different categories of anxiety status. Academic performances have been found affected by the different categories of anxiety as well. It can be concluded that anxiety should be reduced for the betterment of their academic performance and mental strength and ultimately to produce quality physicians to serve the community.BJME, Volume-16, Issue-01, January 2025: 49-60